4z+3=6+2z
solve the question
Answers
Answered by
2
Answer:
Very simple dear
Step-by-step explanation:
4z+3=6+2z
4z-2z=6-3
2z=3
z=3/2
be happy with ur family
lot of love dear
if it is correct then.............
Answered by
0
Answer:
=> The value of z is
Step-by-step explanation:
Given that:-
To find:- The value of the expression,
We must use the transposition method to determine the value of x:
As we have,
=>
First, we need to rearrange the terms,
=>
Now subtract both sides by ,
=>
Simplifying it further, we get
=>
By performing subtraction,
=>
Subtract both sides by ,
=>
=>
Divide both sides by ,
=>
Hence, the required solution is
Similar questions
English,
4 months ago
India Languages,
4 months ago
Math,
4 months ago
Math,
8 months ago
English,
8 months ago
Math,
1 year ago
Environmental Sciences,
1 year ago
English,
1 year ago